Utvärdering av strömaterial av restprodukter från wellpapp - Haglund, Magnus (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2010)
SUMMARY For thousands of years horses have been at people's side. They have been used for transportation at war, to save time, manpower and money. For practical reason, man has forced the horses into narrow spaces. Stabling includes factors as feeding and bedding. In the boxes the bedding materials must be kept clean and maintain good hygiene. Common bedding materials in Sweden are wood shavings, straw and peat. Alternative bedding materials such as newspaper and pelleted straw have been introduced to the market. American studies have shown that pelleted recycled newspaper has great potential as bedding to horses. In recent years the supply have been reduced and prices have increased on traditional bedding material, consequently other options are needed. New bedding materials that are made of residuals from production of cardboard in the form of pellets or flakes have just been or will be introduced to the market. These new materials have not been studied in daily horse management. The aim was to study these new bedding materials to see if they paid off in the long run and if the stable environment was satisfactory. The study had three main questions. Is the working time shorter for the new bedding materials? Is the stable environment satisfactory in relation to Swedish animal welfare legislation? Which of the bedding material has the best economical pay-off? The study tested three new bedding of cardboard (“mix”, “pellets” and “cardboard”) and wood shavings were used as control. There were four groups of six horses in each group during eight weeks of the study. The experiment was located in the White stable in the National Equestrian Centre at Strömsholm. The boxes were cleaned twice a day, once in the morning and once in the afternoon by nine students and a groom (all with previous experience of stable duties) on a rotational basis where two to four people attended each time. The working time of cleaning the boxes and adding fresh bedding materials were noted. Ammonia concentration was measured in each box, three times during a study with one week a part. A test was made to measure how many times each bedding material could absorb its own weight of water. The data were processed statistically and the significance level was set at p <0.05. Analysis of variance was done to find significant differences between treatments and where appropriate significant differences were followed with post-hoc test (Holm-Sidak). The study showed that the best option was the “mix” with good absorption, shortest time for cleaning boxes and had the least bedding material consumption during a study of eight weeks. The “pellets” had the best absorption with six times its own weight. During the phase of establishment more “pellets” was needed than the other bedding materials, but it levelled out in the study since it was not necessary to fill any “pellets” at all in the first two weeks. The “cardboard” (flings) was more expensive than the other materials, had lower absorption and a greater bedding material consumption than that of the other bedding materials. The study had two hypotheses. The first, "Bedding materials of cardboard give shorter working time than for wood shavings", was accepted for cleaning boxes but not for adding additional material. The second, "Bedding materials of cardboard provide satisfactory stable environment", was accepted. In conclusion, the wood shavings had the lowest cost per box considering time for work and amount of bedding material. The new bedding materials were easy to handle, had a positive impact on working time and gave a satisfactory stable environment. However, the price is currently too high for the new bedding materials should be economically successful. Therefore, the price would be lowered so that the new materials could have a better introduction to the market.